2018
DOI: 10.15406/frcij.2018.06.00253
|View full text |Cite
|
Sign up to set email alerts
|

Stature estimation from digit length, bi-acromian and bi-illiac length: a study among two populations from eastern and north eastern India

Abstract: Background: Identification of human remains in medico-legal situation contribution of forensic anthropology is imperative. Forensic anthropology deals with identification of age, sex and ethnicity. Apart from that estimation of stature is found to be one of the major parameters of forensic anthropology, is an essential element of medico-legal investigations when identifications of unknown dismembered remains are involved. The publication regarding estimation of statute seems to be scanty from Eastern India and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…Our attempt to find correlation between length of index and ring finger with the stature of males and females showed statistically significant positive correlation between them, which was valuable in estimating the stature of a Nepalese adult. Similar findings have been documented by many researchers [1,[4][5][6][7][8][9][10][11][12][13][14][15][16]22] but stature and body parts ratio being a population specific trait we pioneered to formulate a simple linear regression equation to ascertain stature from 2DL and 4DL in Nepalese population.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our attempt to find correlation between length of index and ring finger with the stature of males and females showed statistically significant positive correlation between them, which was valuable in estimating the stature of a Nepalese adult. Similar findings have been documented by many researchers [1,[4][5][6][7][8][9][10][11][12][13][14][15][16]22] but stature and body parts ratio being a population specific trait we pioneered to formulate a simple linear regression equation to ascertain stature from 2DL and 4DL in Nepalese population.…”
Section: Discussionsupporting
confidence: 77%
“…In situations where sophisticated methods are not available or where such methods have limitations, simple anthropological methods can have much usefulness [1]. Many studies have revealed the usefulness of finger measurements in stature estimation [1,[4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%